2013
DOI: 10.5539/jas.v5n10p123
|View full text |Cite
|
Sign up to set email alerts
|

Potato (Solanum tuberosum L.) and Sulla (Hedysarum coronarium L.) Intercropping in Tunisia: Effects in Water Consumption and Water Use Efficiency

Abstract: This experiment was carried out at the Technical Center of Potato (C.T.P) situated in the low valley of Medjerda river at Tunisia, during two growing seasons (2006-2007) and (2008-2009). It aims at evaluating the effect of intercropping potato (Solanum tuberosum cv. Spunta) and sulla (Hedysarum coronarium L. cv. Bikra 21) grown under 1:1 intercropping row arrangement and sole cropping on water consumption and water use efficiency of one potato variety and one sulla variety. In addition, land equivalent ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Under intercropping, crops can achieve a more effective complementarity in the use of environmental resources such as land (Gitari et al, 2020; Maitra et al, 2020; Mead & Willey, 1980), nutrients (Gao et al, 2014; Mei et al, 2012), water (Meixiu et al, 2020; Ren et al, 2016; Rezig et al, 2013; Wang et al, 2015, 2020), and light (Raza et al, 2019; Wang et al, 2015), especially when there is a temporal and spatial exploration of these resources (Brooker et al, 2014; Dong et al, 2018; Duchene et al, 2017; Glaze‐Corcoran et al, 2020; Nyawade et al, 2020; Raza et al, 2021; Rigal et al, 2020; Rigal et al, 2020). Although several studies have found a reduction in coffee yield when grown under intercropping with trees (Araújo et al, 2016; Rigal, Xu, Hu, et al, 2020; Rigal, Xu, & Vaast, 2020; Snoeck et al, 2013; Steiman et al, 2011), recent research has demonstrated that depending on the companion tree species used and their spatial arrangement, intercropping of the Arabica coffee can be quite efficient (Perdoná & Soratto, 2015b, 2016, 2020; Rigal, Xu, Hu, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Under intercropping, crops can achieve a more effective complementarity in the use of environmental resources such as land (Gitari et al, 2020; Maitra et al, 2020; Mead & Willey, 1980), nutrients (Gao et al, 2014; Mei et al, 2012), water (Meixiu et al, 2020; Ren et al, 2016; Rezig et al, 2013; Wang et al, 2015, 2020), and light (Raza et al, 2019; Wang et al, 2015), especially when there is a temporal and spatial exploration of these resources (Brooker et al, 2014; Dong et al, 2018; Duchene et al, 2017; Glaze‐Corcoran et al, 2020; Nyawade et al, 2020; Raza et al, 2021; Rigal et al, 2020; Rigal et al, 2020). Although several studies have found a reduction in coffee yield when grown under intercropping with trees (Araújo et al, 2016; Rigal, Xu, Hu, et al, 2020; Rigal, Xu, & Vaast, 2020; Snoeck et al, 2013; Steiman et al, 2011), recent research has demonstrated that depending on the companion tree species used and their spatial arrangement, intercropping of the Arabica coffee can be quite efficient (Perdoná & Soratto, 2015b, 2016, 2020; Rigal, Xu, Hu, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acidic metabolites are produced by intercropping plants with alfalfa and soybeans, resulting in a decrease in pH. These acids act as main osmotic pressure regulators, contributing to the increased SWC in intercropping ( Rezig et al., 2013 ). Our results also showed that intercropping with legumes increases soil SWC, which is supported by previous studies indicating that intercropping systems can significantly improve soil physicohydraulic properties and optimize soil structure ( Chen et al., 2019 ; Shen et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Black and Ong (2000) reported that, compared with monocropping, intercropping reduced crop water consumption (WC) without affecting total biomass production. Rezig et al (2013) also showed that intercropping led to WC reduction in potato and sulla, resulting in increased water use efficiency of both crops. This phenomenon can be attributed to two factors.…”
Section: Introductionmentioning
confidence: 91%